Pengembangan Media Vidio Berbasis Powtoon dan Discovery Learning pada Materi Keanekaragaman Hayati Kelas X di SMAN 1 Batusangkar - Saputri, Ulfa; Marneli, Diyyan; Adriany, Vanny; Fauzana; Apriliya, Marta (Biosel Biology Science and Education, 2025)
The use of varied media and learning models can support the achievement of learning objectives. The aim of this research is to produce video media based on Powtoon and discovery learning on class X biodiversity material at SMAN 1 Batusangkar that is valid and practical. Research research is development research or (R&D) using the 4D model (Define, Design, Develop and Disseminate). The instruments used were interview sheets, validity questionnaires and practicality questionnaires. Validity and practicality results were analyzed using descriptive statistics. The results of the research show that the video media based on Powtoon and discovery learning that was developed fulfills all aspects according to the characteristics of a learning media. The video media developed is very valid with a percentage score of 88.98% and very practical with a score of 93.94% from educators and 87.05% from students. Powtoon-based video media and discovery learning on biodiversity material can be used in learning activities. Keywords: Media, Video, Powtoon, Discovery Learning, Biodiversity